2013
DOI: 10.1016/j.diagmicrobio.2012.11.018
|View full text |Cite
|
Sign up to set email alerts
|

An alternative in vitro drug screening test using Leishmania amazonensis transfected with red fluorescent protein

Abstract: Fluorescent and colorimetric reporter genes are valuable tools for drug screening models, since microscopy is labor intensive and subject to observer variation. In this work, we propose a fluorimetric method for drug screening using red fluorescent parasites. Fluorescent Leishmania amazonensis were developed after transfection with integration plasmids containing either red (RFP) or green fluorescent protein (GFP) genes. After transfection, wild-type (LaWT) and transfected (LaGFP and LaRFP) parasites were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 59 publications
0
26
0
2
Order By: Relevance
“…In 2001, it was reported that EGFP expression by recombinant Leishmania mexicana delayed lesion development (Bennett et al 2001;Millington et al 2010). In contrast, recombinant Leishmania amazonensis GFP kept the infectivity potential (Rocha et al 2013) and recombinant L. amazonensis LUC showed more infectivity but not significant in comparison with wild-type (Reimão et al 2013). However, neither of these studies evaluated immune response factors correlating with infectivity of these recombinant parasites.…”
Section: Discussionmentioning
confidence: 92%
“…In 2001, it was reported that EGFP expression by recombinant Leishmania mexicana delayed lesion development (Bennett et al 2001;Millington et al 2010). In contrast, recombinant Leishmania amazonensis GFP kept the infectivity potential (Rocha et al 2013) and recombinant L. amazonensis LUC showed more infectivity but not significant in comparison with wild-type (Reimão et al 2013). However, neither of these studies evaluated immune response factors correlating with infectivity of these recombinant parasites.…”
Section: Discussionmentioning
confidence: 92%
“…Even though flow cytometry has the disadvantage over fluorometer plate readers of only providing end-point data, it permits measuring different fluorescent signals on the same cell event. In our hands as well as in recent reports, sensitivity of the fluorometer requires large amounts of fluorescent parasites or high infection rates that do not mimic physiological situations as well as prolonged culture times (Rocha et al, 2013). The assay described here uses non-irradiated dividing cells are used and can be adapted to any cell type (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages were exposed to stationary phase promastigotes (2 × 10 6 /well) at a final ratio of 1 : 10. The plates were incubated at 37°C, 5% CO 2, for 5 h in BOD to allow internalization of parasites [13]. Then, the medium was removed for the remaining noninternalized parasites.…”
Section: Methodsmentioning
confidence: 99%